Amifostine alleviates ionizing radiation-induced small intestinal motility dysfunction in mice by remodeling the structure of the enteric nervous system - Sha-Sha Tao; Yan Li; Fei Li; Yan Wang; Meng-Ying Li; Qian Zhang; Yun-Qing Li (Histochemistry and Cell Biology, 2026)

Quantifying the light interception and canopy photosynthesis of strip intercropping system based on 3D canopy photosynthesis model - Si-Rong Huang; Qing-Feng Song; Zheng Guo; Qiu-Feng Long; Li-Sha Zhang; Yue Li; Yuan Yang; Xiao-Chun Wang; Feng Yang; Tai-Wen Yong; Jiang Liu; Yan-Hong Yan; et al. (Computers and Electronics in Agriculture, 2026)

A PINN-based hybrid model with APIDr for interpretable and cross-scenario landslide displacement prediction - Qing Ling; Weidong Chen; Qin Zhang; Li Wang; Wei Qu; Bao Shu; Junguang Ren; Qi Guo; Jiebo Qu; Weizhi Li; Chenjian Yang; Yiming Chen; et al. (Journal of Hydrology, 2026)

Microwave pretreatment assisted regulation of surface oxygen density and narrow micropores of bamboo-based porous carbon for effective CO2 capture and H2 adsorption - Wanying Wang; Lishu Shao; Yongzhen Li; Xiancheng Ma; Weigang Zhao; Lei Li; Sha Luo; Yu Liao; Yan Qing (Journal of Environmental Chemical Engineering, 2026)

Speciated emissions of full-volatility organic compounds from plastic manufacturing: atmospheric impacts and toxicity generation - Dongyang Wu; Qing’e Sha; Luyun Liu; Citao Zhang; Shan Jiang; Qing Guo; Junhao Xu; Jialin Song; Renjun Li; Liufen Cai; Haoqi Chen; Guanghui Li; et al. (Journal of Environmental Sciences, 2026)

A Multi-omics Atlas of Gonadal Sex Differences and Characterization of the dmrt1 Gene in Gymnocypris Eckloni Herzenstein - Luo Lei; Yinhua Zhou; Qing Liu; Hejiao Li; Wuga Sha; Chaoyang Li; Suxing Fu; Yuting Duan; Rongrong Liao; Can Liu; Dapeng Gu; Linzhen Li; et al. (Marine Biotechnology, 2026)

Genome-wide identification of the laccase gene family in wheat (Triticum aestivum L.) during Fusarium pseudograminearum infection - Li-Yu Chen; Yi Diao; Ju-Hong Ma; Xiang-Xue Zhang; Rui Li; Yan Liu; Hong-Tao Tang; Zhi Wang; Sha Gao; Rui-Huan Xu; Zhen-sheng Kang; De-Jun Han; et al. (Plant Science, 2026)

Intranasal biomimetic vesicle platform reprograms the glioblastoma microenvironment for enhanced immunotherapy - Shuo Li; Chao Qin; Fan-Yu Qian; Jin-Hao Wang; Xiang-Gui Wu; Wen-Qing Li; Tai-Yu Liu; Zhao-Jie Chen; Bei-Yuan Zhang; Qi-Yue Liu; Li-Sha Liu; Li-Fang Yin (Chemical Engineering Journal, 2026)

Two new compounds isolated from a sponge-derived fungus Diaporthe sp. ZYX-Z-582 - Jia-Le Chang; Qing-Yun Ma; Li Yang; Qing-Yi Xie; Hai-Tao Li; Jiao-Cen Guo; Hao-Fu Dai; Sha-Sha Liu; You-Xing Zhao (Phytochemistry Letters, 2026)

Associations of prenatal exposure to organophosphate, pyrethroid, and neonicotinoid insecticides with maternal and infant urinary reproductive hormones - Ying Li; Ying Jiang; Ruizhen Li; Sha Huang; Ruijia Li; Qing Guo; Pei Leng; Rui Ma; Dingye Zheng; Yuanyuan Li; Shunqing Xu; Wei Xia (Journal of Hazardous Materials, 2026)

Numerical investigation on the influence of temperature on combustion and emission characteristics of NH3/H2/CH4 mixtures under gas turbine conditions - Yanfei Zhang; Qing Hao; Mingming Huang; Zhenxian Liu; Qin Li; Zewen Yu; Jianfang Du; Xiao Zhang; Zhuoming Xiong; Qingkui Zhang; Yumeng Cao; Haoxi Sha (Fuel, 2026)

Ti3C2-Cl-Bi12O17Cl2/Bi12O17Cl2 Mott-Schottky heterojunction with mixed noncovalent/covalent type to boost ultra-sensitive photoelectrochemical sensing of ciprofloxacin - Chu-Chu Hu; Qi-E Zhang; Shao-Peng Shi; Guo-Qing Zhao; Yan-Sha Gao; Ping Liu; Xun-Kuan Ye; Yan Pan; Hui-Qing Lv; Li-Min Lu (Chemical Engineering Journal, 2026)

Emission characteristics of full-volatility organic compounds from China's aluminum-products industry and their impacts on secondary organic aerosol and ozone potentials - Dongyang Wu; Qing'e Sha; Shan Jiang; Luyun Liu; Citao Zhang; Jialin Song; Junhao Xu; Haoqi Chen; Guanghui Li; Zhangmin Xiang; Bin Jiang; Zhuangmin Zhong; et al. (Environmental Research, 2025)

IFNGR1, IRF8 genetic polymorphisms modulate the susceptibility of non-tuberculous mycobacteria pulmonary disease and influence the patients’ treatment outcomes and immune status - Li-ping Cheng; Zhi-bin Liu; Lei Wang; Jie Cao; Qing-rong Qu; Hai Lou; Xiao-na Shen; Juan Yang; Yuanyuan Yu; Rui Juan Zheng; Wei Sha; Qin Sun (Inflammation Research, 2025)

Establishment of succinic acid production in recombinant Kluyveromyces marxianus enhanced by AI-guided enzyme specificity engineering and redox-controlled fermentation optimization - Du-Wen Zeng; Yi-Fan Zhu; Yuan-Hong Jiang; Ya-Hao Ding; Zhen-Zhi Wang; Kai Li; Sha Liao; Ya-Chao Fan; Lin Zhang; Yu Guang Wang; Xin-Qing Zhao (Chemical Engineering Journal, 2025)

Microplastics and human health: Exposure pathways, toxicity mechanisms, and future research challenges - Zhi Wang; Nuo Li; Yongcheng Ding; Na Li; Menghan Su; Congcong Zhang; Yiqun Li; Qing Wang; Chenyan Sha; Bing Xia; Jie Cheng; Guan Jiang (Journal of Environmental Chemical Engineering, 2025)

Hepatotoxic effects of exposure to different concentrations of Dibutyl phthalate (DBP) in Schizothorax prenanti: Insights from a multi-omics analysis - Luo Lei; Wuga Sha; Qing Liu; Shidong Liu; Yinhua Zhou; Rundong Li; Yuting Duan; Suxing Fu; Hejiao Li; Rongrong Liao; Linzhen Li; Rongzhu Zhou; et al. (Aquatic Toxicology, 2025)

Cascading environmental, phenological, and physiological influences on spatial variability of annual gross primary productivity in the Northern Hemisphere - Lang Han; Gui-Rui Yu; Zhi Chen; Qiu-Feng Wang; Xian-Jin Zhu; Wei-Kang Zhang; Tie-Jun Wang; Zhi-Feng Yan; Tian-You Zhang; Shi-Ping Chen; Hui-Min Wang; Jun-Hua Yan; et al. (Science of The Total Environment, 2025)

Forest thinning effects on soil carbon stocks and dynamics: Perspective of soil organic carbon sequestration rates - Qing Qu; Hongwei Xu; Lin Xu; Chengming You; Bo Tan; Han Li; Li Zhang; Lixia Wang; Sining Liu; Zhenfeng Xu; Sha Xue; Minggang Wang (CATENA, 2025)

Effect of materials types of water-land junction settings on soil bacterial community structure in Shanghai riverside ecological corridor - Wei Guan; Songshuo Li; Qing Wang; Chenyan Sha; Jinghua Su; Min Wang; Ming Nie; Meng Lu (Ecological Engineering, 2025)

Membrane transport engineering for efficient yeast biomanufacturing - Xin-Yue Li; Ming-Hai Zhou; Du-Wen Zeng; Yi-Fan Zhu; Feng-Li Zhang; Sha Liao; Ya-Chao Fan; Xin-Qing Zhao; Lin Zhang; Feng-Wu Bai (Bioresource Technology, 2025)

PBAT biodegradable microplastics enhanced organic matter decomposition capacity and CO2 emission in soils with and without straw residue - Sha Chang; Chao Chen; Qing-Long Fu; Aoyu Zhou; Zhuyao Hua; Fengxiao Zhu; Shiyin Li; Huan He (Journal of Hazardous Materials, 2024)

Levels, sources, and health risk assessment of phthalate acid esters in indoor dust of various microenvironments in university - Jun Pan; Xin Li; Ping Ding; Haojie Luo; Sha Cai; Qing Ge; Liuyi Zhang; Guocheng Hu (Chemosphere, 2024)

Multi-omics insights into the function and evolution of sodium benzoate biodegradation pathway in Benzoatithermus flavus gen. nov., sp. nov. from hot spring - Chao-Jian Hu; Yi-Qing Lv; Wen-Dong Xian; Jian-Yu Jiao; Zheng-Han Lian; Sha Tan; Meng-Meng Li; Zhen-Hao Luo; Ze-Tao Liu; Ai-Ping Lv; Lan Liu; Mukhtiar Ali; et al. (Journal of Hazardous Materials, 2024)

Conformational transformation of activator strand directly regulates CRISPR/Cas12a system activity for live cell sensing of multiple biomolecules - Qing-Nan Li; Dong-Xia Wang; Zhi-Qi Dai; Shun-Li Wu; Gui-Mei Han; Sha Lu; Li-Na Zhu; Hong-Xin Jiang; De-Ming Kong (Chemical Engineering Journal, 2024)

High dimensional proteomic mapping of bone marrow immune characteristics in immune thrombocytopenia - Feng-Qi Liu; Qing-Yuan Qu; Ying Lei; Qi Chen; Yu-Xiu Chen; Meng-Lin Li; Xue-Yan Sun; Ye-Jun Wu; Qiu-Sha Huang; Hai-Xia Fu; Yuan Kong; Yue-Ying Li; et al. (Science China Life Sciences, 2024)

Deeper root distribution and optimized root anatomy help improve dryland wheat yield and water use efficiency under low water conditions - Pu-Fang Li; Bao-Luo Ma; Xiao-Fei Wei; Sha Guo; Yong-Qing Ma (Plant and Soil, 2024)

Preparation and evaluation of liquorice (Glycyrrhiza uralensis) and ginger (Zingiber officinale) kombucha beverage based on antioxidant capacities, phenolic compounds and sensory qualities - Ruo-Gu Xiong; Dan-Dan Zhou; Jin Cheng; Si-Xia Wu; Adila Saimaiti; Si-Yu Huang; Qing Liu; Ao Shang; Hua-Bin Li; Sha Li (International Journal of Gastronomy and Food Science, 2024)

Stay in touch with the endoplasmic reticulum - Sha Sun; Gan Zhao; Mingkang Jia; Qing Jiang; Shulin Li; Haibin Wang; Wenjing Li; Yunyun Wang; Xin Bian; Yan G. Zhao; Xun Huang; Ge Yang; et al. (Science China Life Sciences, 2024)

Histone methyltransferase KMT2D inhibits ENKTL carcinogenesis by epigenetically activating SGK1 and SOCS1 - Yue-Hua Zhang; Qing Tao; Wen-Yan Zhang; Sha Zhao; Wei-Ping Liu; Li-Min Gao (Genes & Genomics, 2024)

Ecosystem responses dominate the trends of annual gross primary productivity over terrestrial ecosystems of China during 2000–2020 - Xian-Jin Zhu; Gui-Rui Yu; Zhi Chen; Wei-Kang Zhang; Lang Han; Qiu-Feng Wang; Hua Qi; Meng Yang; Zhao-Gang Liu; Xiao-Jun Dou; Le-Xin Ma; Shi-Ping Chen; et al. (Agricultural and Forest Meteorology, 2023)

Direct identification of total and missing OH reactivities from light-duty gasoline vehicle exhaust in China based on LP-LIF measurement - Xuehui Liu; Zibing Yuan; Qing'e Sha; Shengrong Lou; Hongli Wang; Xin Li; Junyu Zheng; Bin Yuan; Min Shao (Journal of Environmental Sciences, 2023)

Hierarchical wood cells impose well-textured carbon nanotubes with cobalt single atoms: Bioinspired construction and application in zinc–air battery - Yangyang Chen; Ying Wu; Lei Li; Yu Liao; Sha Luo; Han Xu; Yiqiang Wu; Yan Qing (Chemical Engineering Journal, 2023)

Effects of phenolic acid analogs on the structure, iron oxidation/iron release, and stability of phytoferritin - Jiangnan Hu; Lina Shi; Lei Zhu; Xinmei Sha; Yue Li; Junrui Ma; Qing Zhang; Rui Yang (Food Bioscience, 2023)

Two new bibenzyls from Pleione grandiflora (Rolfe) Rolfe and their antioxidant activity - Wei Li; Jia-Rui Fu; Li-Jun Zheng; Lin Ni; Jun-Qing Liu; Jun-Wen Zhai; Zhuang Zhou; Sha-Sha Wu (Natural Product Research, 2023)

Specific pupylation as IDEntity reporter (SPIDER) for the identification of protein-biomolecule interactions - He-Wei Jiang; Hong Chen; Yun-Xiao Zheng; Xue-Ning Wang; Qingfeng Meng; Jin Xie; Jiong Zhang; ChangSheng Zhang; Zhao-Wei Xu; Zi-Qing Chen; Lei Wang; Wei-Sha Kong; et al. (Science China Life Sciences, 2023)

One-step extraction and solidification of uranium (VI) from sulfate leaching liquor using bifunctional ionic liquids - Fang Zhang; Qiang Wu; Jia-Xuan Yan; Lei-Tao Sha; Yang Li; Xu-Xin Li; Qing-Gang Huang; Ze-Yi Yan (Journal of Environmental Chemical Engineering, 2023)

Polysulfides manipulation: Constructing g-C3N4 networks encapsulated into natural wood fibers for high-performance lithium–sulfur batteries - Yangyang Chen; Ying Wu; Lei Li; Yu Liao; Sha Luo; Yiqiang Wu; Yan Qing (Chemical Engineering Journal, 2023)

Maternal exposure to 4-vinylcyclohexene diepoxide during pregnancy induces subfertility and birth defects of offspring in mice - Wei Song; Ang Li; Qian-Qian Sha; Shao-Yuan Liu; Yong Zhou; Chang-Yin Zhou; Xue Zhang; Xiao-Zhen Li; Jia-Xin Jiang; Fei Li; Chao Li; Heide Schatten; et al. (Science of The Total Environment, 2023)

Mapping Chinese annual gross primary productivity with eddy covariance measurements and machine learning - Xian-Jin Zhu; Gui-Rui Yu; Zhi Chen; Wei-Kang Zhang; Lang Han; Qiu-Feng Wang; Shi-Ping Chen; Shao-Min Liu; Hui-Min Wang; Jun-Hua Yan; Jun-Lei Tan; Fa-Wei Zhang; et al. (Science of The Total Environment, 2023)

Andrographolide ameliorates hepatic steatosis by suppressing FATP2-mediated fatty acid uptake in mice with nonalcoholic fatty liver disease - Li-Sha Ran; Ya-Zeng Wu; Yi-Wen Gan; Hong-Lian Wang; Li-Juan Wu; Chun-Mei Zheng; Yao Ming; Ran Xiong; Yong-Lin Li; Shi-Hang Lei; Xue Wang; Xiao-Qing Lao; et al. (Journal of Natural Medicines, 2023)
Excessive intrahepatocellular lipid accumulation or steatosis is caused by abnormal lipid metabolism and a common character of nonalcoholic fatty liver disease (NAFLD), which may progress into cirrhosis and hepatocellular cancer. Andrographolide (Andro) is the primary active ingredient extracted from Andrographis paniculata , showing a protective role against dietary steatosis with the mechanism not fully understood. In this study, we showed that administration of Andro (50, 100, and 200 mg/kg/day for 8 weeks, respectively) attenuated obesity and metabolic syndrome in high-fat diet (HFD)-fed mice with improved glucose tolerance, insulin sensitivity, and reduced hyperinsulinemia, hyperglycemia, and hyperlipidemia. HFD-fed mice presented hepatic steatosis, which was significantly prevented by Andro. In vitro, Andro decreased the intracellular lipid droplets in oleic acid-treated LO2 cells. The selected RT-PCR array revealed a robust expression suppression of the fatty acid transport proteins (FATPs) by Andro treatment. Most importantly, we found that Andro consistently reduced the expression of FATP2 in both the oleic acid-treated LO2 cells and liver tissues of HFD-fed mice. Overexpression of FATP2 abolished the lipid-lowering effect of Andro in oleic acid-treated LO2 cells. Andro treatment also reduced the fatty acid uptake in oleic acid-treated LO2 cells, which was blunted by FATP2 overexpression. Collectively, our findings reveal a novel mechanism underlying the anti-steatosis effect of Andro by suppressing FATP2-mediated fatty acid uptake, suggesting the potential therapeutic application of Andro in the treatment of NAFLD. Graphical abstract

MamZ protein plays an essential role in magnetosome maturation process of Magnetospirillum gryphiswaldense MSR-1 - Sha Wu; Qing Wang; Xu Wang; Ruixue Guo; Tongwei Zhang; Yongxin Pan; Feng Li; Ying Li (Journal of Oceanology and Limnology, 2021)

Short-term waterlogging-induced autophagy in root cells of wheat can inhibit programmed cell death - Li-Lang Zhou; Kai-Yue Gao; Li-Sha Cheng; Yue-Li Wang; Yi-Keng Cheng; Qiu-Tao Xu; Xiang-Yi Deng; Ji-Wei Li; Fang-Zhu Mei; Zhu-Qing Zhou (Protoplasma, 2021)

Traits, strategies, and niches of liana species in a tropical seasonal rainforest - Qi Liu; Frank J. Sterck; Jiao-Lin Zhang; Arne Scheire; Evelien Konings; Min Cao; Li-Qing Sha; Lourens Poorter (Oecologia, 2021)
Plant functional traits and strategies hold the promise to explain species distribution, but few studies have linked multiple traits to multiple niche dimensions (i.e., light, water, and nutrients). Here, we analyzed for 29 liana species in a Chinese tropical seasonal rainforest how: (1) trait associations and trade-offs lead to different plant strategies; and (2) how these traits shape species’ niche dimensions. Eighteen functional traits related to light, water, and nutrient use were measured and species niche dimensions were quantified using species distribution in a 20-ha plot combined with data on canopy gaps, topographic water availability, and soil nutrients. We found a tissue toughness spectrum ranging from soft to hard tissues along which species also varied from acquisitive to conservative water use, and a resource acquisition spectrum ranging from low to high light capture and nutrient use. Intriguingly, each spectrum partly reflected the conservative–acquisitive paradigm, but at the same time, the tissue toughness and the resource acquisition spectrum were uncoupled. Resource niche dimensions were better predicted by individual traits than by multivariate plant strategies. This suggests that trait components that underlie multivariate strategy axes, rather than the plant strategies themselves determine species distributions. Different traits were important for different niche dimensions. In conclusion, plant functional traits and strategies can indeed explain species distributions, but not in a simple and straight forward way. Although the identification of global plant strategies has significantly advanced the field, this research shows that global, multivariate generalizations are difficult to translate to local conditions, as different components of these strategies are important under different local conditions.

The effect of aging on VEGF/VEGFR2 signal pathway genes expression in rat liver sinusoidal endothelial cell - Wan-Li Wang; Xing-Long Zheng; Qing-Shan Li; Wen-Yan Liu; Liang-Shuo Hu; Huan-Chen Sha; Kun Guo; Yi Lv; Bo Wang (Molecular and Cellular Biochemistry, 2021)

Inhibition of glycolysis ameliorate arthritis in adjuvant arthritis rats by inhibiting synoviocyte activation through AMPK/NF-кB pathway - Ying Wang; Hao Xian; Jiajia Qi; Fang Wei; Xiu Cheng; Sha Li; Qing Wang; Zhaoyang Liu; Yun Yu; Jing Zhou; Xiaojin Sun; Hao Liu; et al. (Inflammation Research, 2020)

Comparison of infrared canopy temperature in a rubber plantation and tropical rain forest - Qing-Hai Song; Yun Deng; Yi -Ping Zhang; Xiao-Bao Deng; You-Xing Lin; Li-Guo Zhou; Xue-Hai Fei; Li-Qing Sha; Yun-Tong Liu; Wen-Jun Zhou; Jin-Bo Gao (International Journal of Biometeorology, 2017)

Associations of hypoxia inducible factor-1α gene polymorphisms with susceptibility to digestive tract cancers: a case–control study and meta-analysis - Zhi-Hai Ni; Xian-Jun Liang; Jing-Gang Mo; Yi Zhang; Jian-Hua Liang; Yu-Sha Yang; Yong Zhou; Zhao-Hua Li; Jian-Liang Zhang; Yin-Lu Ding; Peng Zhang; Jin-Qing Wang (Genes & Genomics, 2015)

Identification of BACH2 as a susceptibility gene for Graves’ disease in the Chinese Han population based on a three-stage genome-wide association study - Wei Liu; Hai-Ning Wang; Zhao-Hui Gu; Shao-Ying Yang; Xiao-Ping Ye; Chun-Ming Pan; Shuang-Xia Zhao; Li-Qiong Xue; Hui-Jun Xie; Sha-Sha Yu; Cui-Cui Guo; Wen-Hua Du; et al. (Human Genetics, 2014)

Cloning and expression analysis of a novel high-mobility group box 2 homologue from Lampetra japonica - Pang Yue; Xiao Rong; Xue Zhuang; Huang Jin Sha; Jin Min Li; Liu Xin; Qing Wei Li (Fish Physiology and Biochemistry, 2014)

The unsaturation of phosphatidylglycerol in thylakoid membrane alleviates PSII photoinhibition under chilling stress - Xiao-lin Sun; Sha Yang; Li-Yan Wang; Qiu-Yu Zhang; Shi-Jie Zhao; Qing-Wei Meng (Plant Cell Reports, 2011)

Determination of Bioactive Matter by Affinity Adsorption Solid Substrate–Room Temperature Phosphorimetry Based on Lectin Labeled with Self-ordered Ring of Eosin Y - Jia-Ming Liu; Zhen-Bo Liu; Wen-Qi Li; Xiao-Mei Huang; Li-Qing Zeng; Jian Sha; Fei-Ming Li (Journal of Fluorescence, 2009)

Isolation of Female-Specific AFLP Markers and Molecular Identification of Genetic Sex in Half-Smooth Tongue Sole (Cynoglossus semilaevis) - Song-Lin Chen; Jing Li; Si-Ping Deng; Yong-Sheng Tian; Qing-Yin Wang; Zhi-Meng Zhuang; Zhen-Xia Sha; Jian-Yong Xu (Marine Biotechnology, 2007)